Kampanye “Isi Piringku” Dan Penerapan Infused Water Sebagai Upaya Pencegahan Stunting Dari Masa Kehamilan - Rini Rahmayanti; Fitri Wahyuni; Darmaji Efrad; Miranda Sari; Siti Afifah; Fatmatul Zahra (IAI Darussalam, 2024)
Andalas sub-district had the highest number of pregnant women in the last three months compared to other sub-districts, namely 185 people with complications of anemia and chronic energy deficiency (CED) of 37 people (20%). Judging from the nutritional status of children under five, the incidence of stunting in this area is still high, namely around 25%, consisting of children under five in the underweight (8.5%), malnourished (7.1%) and stunted (9.4%) categories. . In pregnant women, it was found that education about the nutrition of pregnant women had not been optimal, previously related to the nutrition of pregnant women and the